Respuesta :

Answer:

Step-by-step explanation:

Get the roots first

y  = (x -1)(x - 2)

When y = 0, the two factors in turn can be equated to zero. That gives you the roots

x - 1 = 0        Add 1 to both sides

x = 1

x - 2 = 0       Add 2 to both sides

x = 2

Now you need to worry about the leading coefficient. Just put a 3 in front of the first factor.

y = 3(x - 1)(x - 2)            Remove the brackets.

y = 3(x^2 - x - 2x + 2)    Combine

y = 3(x^2 - 3x - 2)          Remove the brackets.

Answer: y = 3x^2 - 9x - 6

ACCESS MORE